Dampak Privatisasi pada Kinerja Keuangan Badan Usaha Milik Negara - Pratiwi, Dwi Agustin; Malikah, Anik; Anwar, Siti Aminah (e_Jurnal Ilmiah Riset Akuntansi, 2024)
Companies that function well are guaranteed to survive because they gain public trust, thereby providing people with comfort in investing in the company. A company's performance can be measured using various indicators. In this research, profitability is measured by return on equity (ROE), which is the ratio of net profit after tax to equity used to measure the level of return on shareholder investment. The privatization of BUMN in Indonesia explains that privatization causes significant changes in the nature and structure of company owners and management personnel, which ultimately has a significant impact on the performance of the privatized company. BUMN often receive the attention of important parts of society. Due to being too consumptive in the use of existing resources, criminal acts of corruption and poor profitability, BUMN is considered an inefficient business unit. The aim of this research is to find and analyze differences in the financial performance of BUMN before and after privatization.Keywords: Privatization, Financial Performance